PENINGKATAN HASIL BELAJAR IPS TENTANG AKTIVITAS PEMANFAATAN SDA MELALUI PEMBELAJARAN KOOPERATIF TEKNIK SQ3R PADA SISWA KELAS V SDN GLAGAHARUM - Kurniawan, Satunggale; Afifi Rahman, Muhammad (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2024)
The SQ3R learning model in principle stands for the steps of studying a text, which include: First, Survey, namely examining or researching or identifying the entire text. Second, Question, namely compiling a list of questions that are relevant to the text. Third, Read, namely reading the text actively to find answers to the questions that have been arranged. Fourth, Recite, namely memorizing every answer that has been found. Fifth, Review, namely reviewing all the answers to the questions arranged in the second and third steps, we conducted a class action research (CAR) with the following title: "Improvement of social studies learning outcomes regarding natural resource use activities through cooperative learning of the S3QR technique in class students IV Glagaharum Elementary School, Porong District, Academic Year 2023/2024, which focuses on how the activities of class VI students at Glagaharum Elementary School, Porong District in implementing the S3QR technique learning method regarding natural resource utilization activities and the application of the S3QR technique learning method can improve fourth grade students' understanding of natural resource utilization activities in Glagaharum Elementary School, Porong District